Poin Moral dan Sejarah dalam Lagu Anak-Anak - Muhammad Abiel Miladz (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research is titled Moral Point and History in Nursery Rhyme. This research is to describe about the moral point and history inside nursery rhymes “Humpty Dumpty, Ring a Ring of Roses, Jack and jill, London bridge is falling down, and Mary mary quite contrary”. This research used the qualitative approach and using the method of read and write to obtain corresponding datas. To uncover the history and moral point of the nursery rhyme we will be faced with a dark history of the song but that’s what human do move away from those dark history and only take the positive.  Just like how in humpty dumpty we only take the lesson of how fragile we actually are and not how the humpty dumpty is a name of a cannon, or how ring a ring of roses show the positive of being together and not the terror of black death.